Another Look at Guevara’s Poem A una partida qu’el rey don Alfonso fizo de Arévalo - Roger Boase (Revista de Cancioneros Impresos y Manuscritos, 2021)
There are good reasons for taking another look at Guevara’s A una partida qu’el rey don Alfonso fizo de Arévalo. Brian Dutton, Ana María Rodado Ruiz, Óscar Perea Rodríguez and Vicenç Beltran concur that the poem concerns the departure of Isabel of Castile’s brother, Prince Afonso el Inocente, from Arévalo between 1465 and 1468, and this is now generally accepted. However, Patrick Gallagher (1968: 190), in his edition of the poetry of Garci Sánchez de Badajoz, expresses the view that the king in question is Afonso V of Portugal, who, after marrying his neice Juana la Beltraneja in Plasencia, had spent two months in Arévalo in the summer of 1475, plotting with noble dissidents to overthrow Enrique IV of Castile. Gallagher’s opinion, if incorrect, deserves at least to be refuted.